The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1091/mbc.e20-05-0301
|View full text |Cite
|
Sign up to set email alerts
|

Spatial regulation of MCAK promotes cell polarization and focal adhesion turnover to drive robust cell migration

Abstract: The asymmetric distribution of microtubule (MT) dynamics in migrating cells is important for cell polarization, yet the underlying regulatory mechanisms remain underexplored. Here, we addressed this question by studying the role of the MT depolymerase, MCAK, in the highly persistent migration of RPE-1 cells. MCAK knockdown leads to slowed migration and poor directional movement. Fixed and live cell imaging revealed that MCAK knockdown results in excessive membrane ruffling as well as defects in cell polarizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 78 publications
5
8
0
Order By: Relevance
“…The knockdown of MCAK led to an impaired recruitment of FAK and paxillin, two positive key regulators for cell migration [64,65], leading to the reduced phosphorylation of these important FA structure proteins. These results are in accordance with a recently published paper by Zong et al, showing that MCAK knockdown interfered with directional movement, centrosome positioning and increased lifetime of FA's in RPE cells [21]. Moreover, both HeLa and RPE knockdown cells displayed a decreased FA size, which is also a vital factor related to cell migration [41].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The knockdown of MCAK led to an impaired recruitment of FAK and paxillin, two positive key regulators for cell migration [64,65], leading to the reduced phosphorylation of these important FA structure proteins. These results are in accordance with a recently published paper by Zong et al, showing that MCAK knockdown interfered with directional movement, centrosome positioning and increased lifetime of FA's in RPE cells [21]. Moreover, both HeLa and RPE knockdown cells displayed a decreased FA size, which is also a vital factor related to cell migration [41].…”
Section: Discussionsupporting
confidence: 91%
“…The deregulation of its activity leads to severe mitotic defects and chromosomal instability [15,16,18]. In line with the close relationship between the MT and actin cytoskeleton, we and others have shown that functional MCAK has an impact on cancer cell migration [19][20][21]. The inhibitory phosphorylation of Aurora B at serine 192 of MCAK affects the directed migration as well as the invasion capacity of colorectal and cervix carcinoma cell lines [19].…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations